Anticoagulant Properties of Purified X-Like Fragments of Human Fibrinogen Produced by Degradation with Leukocyte Elastase - Sterrenberg, Lydi; van Liempt, Gert Jan; Nieuwenhuizen, Willem; Hermans, Jo (Thrombosis and Haemostasis, 1984)
The anticoagulant properties of fibrinogen digestion products change with stage of digestion. On digestion with leukocyte elastase, in the presence of calcium ions, the anticoagulant potency of fibrinogen digests first increases, then decreases sharply, and in late stages increases again. This is different from plasmin digestion where only an increase in anticoagulant activity is seen followed by a slow decrease.From SDS-gel electrophoresis it appears that both the early rise and the decrease in anticoagulant activity are associated with the stage of elastase-produced X-like fragments. This is confirmed with pure fragments: X-like fragments (purified from elastase digests of fibrinogen of different stages by ammonium sulphate precipitation and ion-exchange chromatography) give an increase and decrease in anticlotting activity which correlates very well with that of the potency of the digest from which they are purified. As expected, and in contrast with (late) plasmic X- fragments, late elastase X-like fragments have a low anticoagulant potency. The molecular basis for the gain and loss in anticoagulant activity going from early to late X-like fragments is obscure. Immunological tests, calcium-binding experiments and affinity chromatography on immobilized thrombin-activated NDSK suggest that the changes in anticoagulant activity are not due to a proteolytic change in the carboxyl-terminal part of the γ-chain in the D moiety of the molecule. Our data suggest a correlation with the stage of digestion of the Aa-chain in the X-like fragments.
Keywords: Fibrinogen degradation product; Elastase; Calcium binding; Anticlotting properties